2023
DOI: 10.3389/fncel.2023.1143319
|View full text |Cite
|
Sign up to set email alerts
|

Adult-specific Reelin expression alters striatal neuronal organization: implications for neuropsychiatric disorders

Abstract: In addition to neuronal migration, brain development, and adult plasticity, the extracellular matrix protein Reelin has been extensively implicated in human psychiatric disorders such as schizophrenia, bipolar disorder, and autism spectrum disorder. Moreover, heterozygous reeler mice exhibit features reminiscent of these disorders, while overexpression of Reelin protects against its manifestation. However, how Reelin influences the structure and circuits of the striatal complex, a key region for the above-ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…In animal models, especially rodents, there have been observed emotional, motor, and learning deficits associated with abnormal reelin levels [56][57][58]. This finding encourages researchers to identify whether normalization of the protein's level might aid disease treatment, and some papers suggest that it might decrease psychopathological symptoms [59][60][61][62].…”
Section: Possible Research Regarding the Reelin Signaling Pathwaymentioning
confidence: 96%
“…In animal models, especially rodents, there have been observed emotional, motor, and learning deficits associated with abnormal reelin levels [56][57][58]. This finding encourages researchers to identify whether normalization of the protein's level might aid disease treatment, and some papers suggest that it might decrease psychopathological symptoms [59][60][61][62].…”
Section: Possible Research Regarding the Reelin Signaling Pathwaymentioning
confidence: 96%
“…Conversely, the overexpression of Reelin protects against psychiatric disease-related phenotypes in mice [179]. Recent experiments using conditional gain and loss of function mouse models showed that the overexpression of Reelin leads to increased numbers of striatal interneurons and dopaminergic projections which could explain the positive outcome of increased Reelin levels on the SCZ phenotype [180].…”
Section: Reelin In Schizophreniamentioning
confidence: 99%